Constantine’s SOLI INVICTO COMITI Coinage: Theme and Variations - Richardson, Gavin T. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
Sometime in AD 310, a mint worker in the provincial Gallic town of Lugdunum (modern Lyon) engraved a reverse die depicting a majestic figure raising his right hand and holding a celestial sphere in his left. The figure wears a spiked, radiate crown and is clothed only by a chlamys, a cape worn by ancient Greek horsemen. The legend in the dative case, SOLI INVICTO COMITI, identifies this figure as Sol, the invictus or unvanquished sun god whose cult was among the most popular in the ancient world. He is further identified as being the comes, or companion, of the figure on the obverse. The fact that this figure was Constantine the Great, known to history as the man who Christianized the Roman Empire, makes this coin as enigmatic as it was ubiquitous, one of the most widespread and enduring numismatic designs of that emperor’s long reign. This essay explores this coin type’s iconographic theme, its variations, and what they both might say about politics and religion in the age of Constantine. In scholarly discussions of his reign, coins are often adduced to illustrate some larger historiographical point. In this essay, I would like to shift that emphasis, rendering the historical context a means to better understand the coins themselves—their origins and style, the way in which traditional solar iconography serves as a foil to set off topical points of emphasis, and the religious and political purposes for their decade-long striking. Perhaps it is too much to say that in the SOLI INVICTO COMITI reverse type we witness the history of Constantine’s age in one coin, but it is not an overstatement to point out that this type touches upon the most prominent events of the early 4th century, whose impact is felt even in the present time.